2003
DOI: 10.1002/pssa.200306394
|View full text |Cite
|
Sign up to set email alerts
|

Magnetism of Co(C3H4N2)2(CO3)(H2O)2

Abstract: We report on a detailed investigation of magnetic susceptibility χ (T, B), magnetization M(T, B) and specific heat Cp(T, B) for a polycrystalline sample of Co(C3H4N2)2(CO3)(H2O)2. Ground state for Co2+ has found to show an unquenched spin–orbit coupling and a weak antiferromagnetic interaction between Co ions. Application of magnetic field significantly affects the magnetization and specific heat at T < 20 K. Anomaly observed in Cp(T, H)‐dependences may be interpreted in terms of the conventional two‐level (do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…An unquenched spin-orbit coupling was assumed to be the reason of a larger m eff in Co(CO 3 )(OH 2 ) 2 (ImH) 2 . 6 Considering the fact that the letter complex has also a larger permittivity 3 0 at room temperature one may suggest that the dielectric properties are associated with the Co 2+ orbitals, which in fact are involved in the dipole of Coligands. When we deal with the Cu(Im) 2 and Zn(Im) 2 complexes, we see that the paramagnetic properties of Cu 2+ (ref.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An unquenched spin-orbit coupling was assumed to be the reason of a larger m eff in Co(CO 3 )(OH 2 ) 2 (ImH) 2 . 6 Considering the fact that the letter complex has also a larger permittivity 3 0 at room temperature one may suggest that the dielectric properties are associated with the Co 2+ orbitals, which in fact are involved in the dipole of Coligands. When we deal with the Cu(Im) 2 and Zn(Im) 2 complexes, we see that the paramagnetic properties of Cu 2+ (ref.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5] Some years ago, we focused our interest on magnetic properties of cobalt complexes with imidazole Co(CO 3 )(H 2 O) 2 (C 3 -H 4 N 2 ) 2 (ref. 6) and [Co(C 3 H 3 N 2 ) 2 ] n . 7 The experimental data revealed that the Co 2+ ions in these compounds behave in a different manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…l -α-amino acids: asparagine, pure, Sigma Chemical Co., histidine, pure (≥99.0%), Fluka Chemie GmbH, alanine, pure, International Enzymes Limited; polymeric [Co(imid) 2 ] n complex prepared by A. Vogt, Faculty of Chemistry, University of Wrocław [27, 38, 45]; potassium nitrate (V), p.a., P.O.Ch. Gliwice; nitric (V) acid, p.a., P.O.Ch.…”
Section: Methodsmentioning
confidence: 99%
“…[Co(imid) 2 ] n is a coordination compound crystallizing in an infinite polymeric net, in which each cobalt(II) ion is joined via imidazole bridges with four adjacent ions of the metal [27, 28]. Each Co(II) ion forms two dative bonds with the nitrogen atoms of two deprotonated imidazole moieties and two ionic bonds with the nitrogen atoms of two other imidazoles (Fig.…”
Section: Introductionmentioning
confidence: 99%